2017
DOI: 10.1039/c7mt00074j
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for widespread, severe brain copper deficiency in Alzheimer's dementia

Abstract: Datasets comprising simultaneous measurements of many essential metals in Alzheimer's disease (AD) brain are sparse, and available studies are not entirely in agreement. To further elucidate this matter, we employed inductively-coupled-plasma mass spectrometry to measure post-mortem levels of 8 essential metals and selenium, in 7 brain regions from 9 cases with AD (neuropathological severity Braak IV-VI), and 13 controls who had normal ante-mortem mental function and no evidence of brain disease. Of the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 95 publications
(123 reference statements)
12
101
0
Order By: Relevance
“…The wet-to-dry weight ratio (R wd ) for the AD samples was 5.9 ± 0.2, which was very similar to that of the healthy controls: R wd = 6.2 ± 0.2. These numbers are in agreement with a previous study which reported no difference in R wd between AD and controls 28 , and when formalin-fixed tissue is used 29 , since formalin fixation does not alter the total water content of the tissue 30 . However, it is worth noting that the white matter contains consistently less, i.e.…”
Section: Squid Magnetometry Experiments and Data Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The wet-to-dry weight ratio (R wd ) for the AD samples was 5.9 ± 0.2, which was very similar to that of the healthy controls: R wd = 6.2 ± 0.2. These numbers are in agreement with a previous study which reported no difference in R wd between AD and controls 28 , and when formalin-fixed tissue is used 29 , since formalin fixation does not alter the total water content of the tissue 30 . However, it is worth noting that the white matter contains consistently less, i.e.…”
Section: Squid Magnetometry Experiments and Data Analysissupporting
confidence: 92%
“…However, the authors failed to found the same difference in the inferior temporal cortex which, on the other hand, reported iron levels correlating with antecedent cognitive decline in those individuals who had underlying plaque and tangle pathology 37 . Total iron levels are known to increase in different brain areas of AD cases 28 , with the temporal cortex being one of the most and earliest affected regions 24,38 . It is not yet clear what the underlying phenomena leading to brain iron accumulation in the context of AD are.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, extraction of samples from specific areas of the brain allows one to determine metal ion concentration differences among the various parts of the brain, to provide an insight into metal distributions between control and AD patients for each brain area. Indeed, because of cessation of blood circulation after death, metals cannot be exchanged post‐mortem among the various tissues so that a spatial picture of metal distributions in the brain is feasible . Intriguing findings with ICP‐MS show that Zn levels are elevated in many areas of AD brains, in accordance with a situation of increased Zn 2+ sequestration in heavily affected brain regions to cause functional unavailability of this metal ion for physiological processes in other areas, regardless of any increase in total tissue‐Zn.…”
Section: Beyond the Aβ Peptides: The Contribution Of Mass Spectrometrmentioning
confidence: 96%
“…Intriguing findings with ICP‐MS show that Zn levels are elevated in many areas of AD brains, in accordance with a situation of increased Zn 2+ sequestration in heavily affected brain regions to cause functional unavailability of this metal ion for physiological processes in other areas, regardless of any increase in total tissue‐Zn. On the contrary, although Cu increase or decrease in AD brains is still a matter of debate, Cu levels have been reported to be depleted in many areas of AD brains to possibly have a significant impact on cellular energy production, as well as to increase oxidative damage in AD brain by impairing Cu‐mediated antioxidant defences such as those catalyzed by superoxide dismutase (SOD) …”
Section: Beyond the Aβ Peptides: The Contribution Of Mass Spectrometrmentioning
confidence: 99%
See 1 more Smart Citation